Technological Leapfrogging: Estonia’s E-Governance Odyssey by using Emerging Technologies and Lesson for Developing States - Khalid, Hamna; Khan, Muhammad Farhan; Qureshi, Summaiyya (Pakistan Languages and Humanities Review, 2024)
The purpose of this study to highlights the journey of Estonia’s e-governance system by launching the Tiger Leap initiative and to examines Estonia’s innovative initiatives comprising, e-banking, digital identity infrastructure (e-ID) and X road system. The main objective of this research is to address the privacy and security issues of Estonian e-services through emerging technologies i.e. Artificial Intelligence and Block chain technology. In the realm of the digital age, Estonia stands out as a pioneer in using Block chain technology and Artificial Intelligence to augment its e-governance framework. A small Baltic state stirred towards the transformation in the early 1990s through digitization and digitalization respectively. The explanatory approach of qualitative research is used and data sampling for this research is conducted by using secondary sources of data consisting of official reports, journal articles, official websites and documents. It provides policies that underdeveloped states can augment their e-governance by using these advance technologies.